Musdah Mulia's Thoughts on Women's Reproductive Rights in Islam - Aziz, Muhammad Hilmi (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2025)
Abstrak: Reproductive rights are a crucial issue that must be advocated for. Musdah Mulia is one of the prominent figures deeply concerned with this matter. This article aims to examine Musdah Mulia's thoughts on reproductive rights and analyze their alignment with the principles of maqāṣid al-sharī‘ah. The study draws from her books, YouTube channel, podcasts, and seminar presentations, which are then analyzed in relation to the objectives of Islamic law. There are seven reproductive rights identified in her discourse: the right to express sexual desire equally with men; the right to refuse sexual intercourse; the right to decide if and when to become pregnant; the right to determine the number of children; the right to choose whether or not to marry; the right to access healthcare services; and the right to obtain accurate and adequate information regarding reproductive rights and health. The protection of these reproductive rights falls under al-maqāṣid al-ḍarūriyyāt, which are the essential objectives of maqāṣid al-sharī‘ah, as women's reproductive rights constitute a fundamental aspect of life that ensures the proper functioning of both religious and human affairs. Neglecting these aspects leads to disorder and injustice..